Adenosine A1 receptor-mediated suppression of carbamazepine-resistant seizure-like events in human neocortical slices - Klaft, Zin-Juan; Hollnagel, Jan-Oliver; Salar, Seda; Caliskan, Gursel; Schulz, Steffen B.; Schneider, Ulf C.; Horn, Peter; Koch, Arend; Holtkamp, Martin; Gabriel, Siegrun; Gerevich, Zoltan; Heinemann, Uwe (Epilepsia, 2016)
Objective The need for alternative pharmacologic strategies in treatment of epilepsies is pressing for about 30% of patients with epilepsy who do not experience satisfactory seizure control with present treatments. In temporal lobe epilepsy (TLE) even up to 80% of patients are pharmacoresistant, and surgical resection of the ictogenic tissue is only possible for a minority of TLE patients. In this study we investigate purinergic modulation of drug-resistant seizure-like events (SLEs) in human temporal cortex slices. Methods Layer V/VI field potentials from a total of 77 neocortical slices from 17 pharmacoresistant patients were recorded to monitor SLEs induced by application of 8 mM [K+] and 50 μm bicuculline. Results Activating A1 receptors with a specific agonist completely suppressed SLEs in 73% of human temporal cortex slices. In the remaining slices, incidence of SLEs was markedly reduced. Because a subportion of slices can be pharmacosensitive, we tested effects of an A1 agonist, in slices insensitive to a high dose of carbamazepine (50 μm). Also in these cases the A1 agonist was equally efficient. Moreover, ATP and adenosine blocked or modulated SLEs, an effect mediated not by P2 receptors but rather by adenosine A1 receptors. Significance Selective activation of A1 receptors mediates a strong anticonvulsant action in human neocortical slices from pharmacoresistant patients. We propose that our human slice model of seizure-like activity is a feasible option for future studies investigating new antiepileptic drug (AED) candidates.
Created from Fastlane, Scopus look-up
Keywords: Epilepsy; Human brain slices; Pharmacoresistance; Seizure models; Temporal lobe